Puberty in four genotypes of femate goats in northeast Brazil - Simplício, Aurino Alves; Figueiredo, Elsio Antonio Pereira de; Riera, Gerardo Simon; Foote, Warren Cristopher (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried out with 99 female kids from four native breeds (Canindé Marota, Moxotó, and Repartida, raised on native pasture at the Brazilian National (loat Research Center, Ceará State, Northeast Brazil. Body weight of the animals were taken at birth, and at four-week intervals until each female kid showed the first puberal estrus. Between 40-60 hours after puberal estrus was detected using teaser bucks, the ovaries of each female kid were observed by laparotomy to determine the number of corpora albicantia and/or corpora hemorrhagica, as an estimate of the occurrence and rate of prepuberal and puberal ovulation, respectively. The overail mean age and live body weight at puberty was 3616±69 days and 12.6±0.2 kg, respectively. Breed or type of birth did not affect significantly (P>0.05) the age and weight at puberty. The ovulation rate at prepuberal period and at puberal estrus was 1.00 and 1.04, respectively (P>0.05). Forty percent of the female kids ovulated prior to puberal estrus and 100% ovulated at puberal estrus. Ovulation occurred more frequentely in the right than in the left ovary at prepuberal (P<0.01) and puberal (P<0.05) respectively.